La sélection des objets à protéger dans les églises de la Reconstruction : l’exemple de la Manche (1944-1974) - Élisabeth Marie (In Situ)
In 1944 more than three hundred churches in the Manche department were destroyed or badly damaged. The reconstruction of these churches took over thirty years, and these reconstructed churches are now recognised as an integral part of the department’s heritage. The services of the Conservation des antiquités et objets d’art has undertaken an inventory of these churches, focussed on 160 buildings and about 130 religious artefacts, along with a collection of stained glass. To begin with, the contents of thirty churches were surveyed in an operation running alongside an inventory of religious buildings carried out by the Historic monuments service of the Basse-Normandie region. These two surveys were followed by measures of statutory protection for forty objects or furnishing ensembles conserved in the department’s churches. There was considerable debate as to the criteria appropriate for the protection of these objects, and two meetings of the departmental commission on the protection of the movable heritage were able to refine these criteria and render them more pertinent.